Pre-failure indicators detected by Acoustic Emission: Alfas stone, cement-mortar and cement-paste specimens under 3-point bending - Stavros K. Kourkoulis; Ioanna Dakanali (Fracture and Structural Integrity)
Acoustic Emission (AE) is the technique most wide¬ly used now¬adays for Structural Health Monitor¬ing (SHM). Application of this technique for continuous SHM of restored elements of stone monuments is a challeng¬ing task. The co-existence of different materials creates interfaces rendering “identi¬fication” of the signals recorded very complicated. To overcome this difficulty one should have a clear overview of the nature of AE signals recorded when each one of the constituent materials is loaded mechanically. In this direction, an attempt is here described to enlighten the signals recorded, in case a series of structural materials (natural and artificial), ex-tensively used for restoration projects of classic monuments in Greece, are subjected to 3-point bending. It is hoped that obtaining a clear understanding of the nature of AE signals re¬corded during these element¬ary tests will provide a valuable tool permitting “identification” and “classification” of signals emitted in case of structural tests. The results appear encouraging. In addition, it is concluded that for all materials tested (in spite their differences in micro¬structure and composition) clear pre-failure indicators are detected, in good accordance to similar indicators pro-vided by other techniques like the Pressure Stimulated Currents (PSC) one.